PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) INDUSTRI KECIL KIMIA BERORIENTASI KEWIRAUSAHAAN UNTUK SMK - Diniaty, Artina; Atun, Sri (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2015)
This study aims for developing students' worksheet of entrepreneurship-oriented small-scale chemical industry, and investigating the quality of entrepreneurship-oriented small-scale chemical industry that is appropriate to be implemented in learning. This study is classified to research and development which refers to Borg & Gall development model. This research consists of four steps: which are introduction, planning, developing, and product evaluation. The product evaluation was conducted by peers, material and media experts, and chemistry teachers. The data collection instruments used validation sheet of the products. The results show that the developed products are in the form of students' worksheet of entrepreneurship-oriented small-scale chemical industry, and the result of the assessment by chemistry teachers shows the average assessment is a good category so that this worksheet is feasible to be used in learning.